Digital Transformation of Rural Tourism Villages: A Systematic Literature Review on Strategies, Challenges, and Opportunities for Sustainable Tourism Development - Joko Haryono,; Nurbaeti,; Sri Sulartiningrum,; Willy Arafah,; Rahmat Ingkadijaya, (Technium Social Sciences Journal, 2025)
This study aims to examine the strategies, challenges, and opportunities for digital transformation in rural tourism villages in the context of sustainable tourism development. Using the Systematic Literature Review (SLR) method, 28 relevant scientific articles indexed by Scopus are explained thematically using a content analysis approach. The results of the study indicate that digital tourism village transformation consists of three main phases: digital empowerment, digital integration, and digital innovation, with strategies that are greatly influenced by technological readiness, socio-cultural capacity, and institutional support. The main challenges in its implementation include low digital literacy, limited infrastructure, cultural resistance, and data privacy issues. However, digitalization presents significant opportunities for community participation, cultural preservation, tourism market expansion, and achieving the United Nations' Sustainable Development Goals (SDGs). The conclusion of this study is the importance of a multidisciplinary and collaborative approach in designing an effective digital village transformation. The suggestion from this study is the need for case study-based field research, as well as the development of a digital readiness evaluation model and a technology-based community empowerment strategy, to effectively and inclusively implement digital tourism village transformation.